Anxiety, depression and insomnia during Covid-19 pandemic among the public in Malaysia: The association with knowledge, attitude and practice (KAP), and social media addiction / Lim Kuok Quan - Lim, Kuok Quan (2021)
Background: The COVID-19 pandemic caused severe distress to the government and the public. The community had to adapt to the movement control order, impacting social interaction, employment, and schooling. The public’s knowledge, attitude, and practice (KAP) of the pandemic and possibly frequent social media usage during sudden and prolonged social isolation might affect one’s mental health. Objectives: The study measured anxiety, depression and insomnia in the participants and its association with knowledge, attitude, practice (KAP) and social media usage during the pandemic. Methods: This cross-sectional online survey study was conducted between April 2020 and June 2020. The participants were from the public who could understand and read adequate Malay or English, and ≥ 18 years old. A total of 353 participants responded and were recruited in the online survey. The participants were assessed using the Knowledge, Attitudes, and Practices towards COVID19 Pandemic (KAP), the Social Media Addiction during COVID-19 pandemic (SMACOP), Insomnia Severity Index, Generalized Anxiety Disorder Scale – 7 (GAD-7), and Patient Health Questionnaire – 9 (PHQ-9). In the KAP, scores of 13 and below were considered low, v while scores more than 13 were adequate. The cut-off point for depression is ≥ 5, and for anxiety is ≥ 6. The multivariate logistic regression analysis was used for the purpose to explore the influential factors. Results: The average age of the participants was 42 years old, and more than half were female (63.5%). Two-thirds of the participants were Chinese, followed by Indian (22.1%), and only about 12% were Malay; 77% of the individuals were still working. Most of the participants were married, and more than 70% had tertiary educational levels and above. More than half the participants (77.3%) were equipped with adequate KAP towards this pandemic and about half of them (45.6%) were classified as social media addicts. There were a considerably high proportion of them had insomnia (34.0) while in 32.0% of the participants experienced symptomatic depression. Anxiety-wise, a total of 89 individuals (25.2%) had symptomatic anxiety. The total KAP was significantly correlated with total insomnia (rho = -0.211; p <0.01), anxiety (rho = -0.187; p <0.01), and depression (rho = -0.169; p <0.01) symptoms. The total social media addiction was fair to moderately correlated with having insomnia (rho = 0.315; p <0.01), anxiety (rho = 0.318; p <0.01), and depression (rho = 0.244; p <0.01). Multivariate analysis revealed that insomnia was significantly related to KAP and SMACOP (95% CI: - 0.0098, -0.007; p = 0.025) and (95% CI: 0.044, 0.087) respectively. For anxiety symptoms, there was significant association with KAP (95% CI: -0.119 to -0.019), SMACOP (95% CI: 0.057, 0.104), age (95% CI: -0.021, -0.008), and being female (95% CI: 0.063, 0.408). For depression symptoms, there was significant association with SMACOP (adjusted B = 0.048, 95% CI: 0.025, 0.070), and age (adjusted B = -0.018, 95% CI: -0.025, -0.011). vi Conclusions: There is significant prevalence of anxiety, depression and insomnia among the public during the COVID-19 pandemic. Knowledge, attitudes, and practices (KAP) regarding the COVID-19 pandemic are crucial in determining the risk of developing mental health issues. The higher the levels of knowledge, attitudes, and practices towards COVID19, the lower the levels of anxiety and insomnia among the public during the COVID-19 pandemic. Misinformation and disinformation adversely affect psychological wellbeing. The higher the levels of social media addiction, the higher the levels of anxiety, depression and insomnia among the public during the COVID-19 pandemic. Thus, all relevant authorities play a pivotal role in disseminating and monitoring facts and misinformation to the general public.